Education On Waste Sorting As A Preventive Effort To Address Waste Problems In The MI NU 03 Kebonagung Environment - M. Hasan al Asrori; Akhilla Rizki Kinanti; Lintang Puji Nur Afifah; Nur Lailatus Syafitra; Nahwa amalia; Putri adhelia; Irman Said Prasetyo (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The effort to maintain cleanliness in our surroundings must start with ourselves by doing small things. Guidance for students regarding environmental issues caused by waste accumulation is necessary to raise their awareness so that they become more concerned about their surroundings. By actively participating, students can cultivate the habit of disposing of waste in its proper place. However, due to the numerous categories of waste, it is necessary to provide guidance to students about the types of waste, namely: organic waste, inorganic waste, and the 3Rs (Reduce, Reuse, Recycle) and their management. Students must be socialized to abandon the old habit of simply throwing away waste, but also to receive guidance and to get accustomed to sorting, selecting, and categorizing waste while implementing the development of waste banks so that they have economic value. If it can be implemented, then the practice of processing waste will be a concrete step in waste management. The socialization was carried out in the form of presentations and other interactive activities. In the future, it is hoped that these small habits can be taught within families and the surrounding community, which would help reduce environmental issues caused by waste